(untitled) (International Journal of Scientific Trends, 2025)
Natural medicinal plants have been widely used in medicine since ancient times. Bioactive substances extracted from them play an important role in the treatment and prevention of various diseases. This article analyzes the scientific literature on the chemical composition, pharmacological effects and medical use of Ziziphora pedicellata Pazij., Glycyrrhiza glabra L. and Plantago major L. plants.